Tata Kelola Kolaboratif dan Komunikasi Strategis dalam Pencegahan Stunting: Analisis Sosiologi Politik atas Peran Pemerintah Kota Ambon - Beay, Lenora; Lopulalan, Dortje Leonora Yokbeth; Kissya, Vransisca (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article investigates the role of the Ambon City Government in stunting prevention through the lens of collaborative governance and strategic health communication. Drawing on a qualitative political sociology approach, the study explores how municipal authorities integrate diverse actors—including the National Population and Family Planning Board (BKKBN), traditional villages (desa and negeri), health institutions, and non-governmental organizations—into a multi-sectoral governance network aimed at reducing stunting prevalence. The research also examines the city’s use of strategic communication tools such as public service announcements (PSAs), billboards, banners, and community outreach programs to influence public behavior and raise awareness about stunting-related health risks. Findings reveal that effective inter-institutional collaboration, reinforced by culturally resonant and consistent communication efforts, significantly contributes to policy coherence and public engagement. Moreover, the allocation of targeted budgets indicates strong political commitment, enhancing policy legitimacy and implementation outcomes. The study contributes to social science and humanities discourse by offering a context-specific analysis from Eastern Indonesia—an area underrepresented in global governance and public health literature. The integration of governance theory, political sociology, and strategic health communication presents a novel interdisciplinary framework for evaluating public health interventions. It also proposes a replicable model of urban collaborative governance applicable to similarly structured socio-political environments in the Global South.